2016
DOI: 10.3945/ajcn.116.135004
|View full text |Cite
|
Sign up to set email alerts
|

Ultraprocessed food consumption and risk of overweight and obesity: the University of Navarra Follow-Up (SUN) cohort study

Abstract: Ultraprocessed food consumption was associated with a higher risk of overweight and obesity in a prospective cohort of Spanish middle-aged adult university graduates. Further longitudinal studies are needed to confirm our results. This trial was registered at clinicaltrials.gov as NCT02669602.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
341
1
40

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(411 citation statements)
references
References 28 publications
29
341
1
40
Order By: Relevance
“…Of the 10 studies [52-61] examining the relationship between ultra-processed foods and obesity or related disease, 3 evaluated data for all age groups [53-55], 3 focused on pediatric populations [57-59], and 4 studied only adults [52, 56, 60, 61]. Evidence was available from several countries across the world, with most studies in Brazil [54, 55, 57-59], and additional evidence from 2 studies in Spain [56, 61], 1 in the UK [52], 1 in Canada [60], and 1 in Guatemala [53].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 10 studies [52-61] examining the relationship between ultra-processed foods and obesity or related disease, 3 evaluated data for all age groups [53-55], 3 focused on pediatric populations [57-59], and 4 studied only adults [52, 56, 60, 61]. Evidence was available from several countries across the world, with most studies in Brazil [54, 55, 57-59], and additional evidence from 2 studies in Spain [56, 61], 1 in the UK [52], 1 in Canada [60], and 1 in Guatemala [53].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence was available from several countries across the world, with most studies in Brazil [54, 55, 57-59], and additional evidence from 2 studies in Spain [56, 61], 1 in the UK [52], 1 in Canada [60], and 1 in Guatemala [53]. Two early studies evaluated food and beverage purchases [53, 54], while most evaluated self-reported dietary intake assessed by food frequency questionnaire (FFQ) [56, 57, 61], 24-hour dietary recalls [58-60], or food records [52, 55]. Almost all investigations defined ultra-processed foods using the NOVA classification system developed by Monteiro and colleagues [54-56, 58, 60, 61].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the studies in this special issue challenge that assertion and demonstrate an association between higher consumption of ultra-processed foods and poorer nutritional intakes, including higher intakes of energy and free/added sugar (9,11) and lower intakes of fibre (9) , micronutrients (9) and protein (8) . Epidemiological evidence has previously demonstrated that ultra-processed food consumption is associated with poorer diet quality in the USA (13) , Canada (14) and Brazil (15) ; obesity in Brazil (16) , Guatemala (17) , Spain (18) and Sweden (19) ; hypertension in Spain (20) ; metabolic syndrome in Brazil (21) ; and dyslipidaemia in children in Brazil (22) . Papers in this special issue reinforce the aetiology between ultra-processed food consumption and nutritional outcomes and chronic conditions, and extend such evidence to new populations.…”
mentioning
confidence: 99%
“…Cohort studies may be used to study long-term outcomes prone to reverse causality, as has been done in a study in Spain which found a positive association between ultraprocessed food consumption and the incidence of overweight and obesity (Mendonça et al, 2016). Because dietary habits may change though out the course of life, we also need to understand if the effects of ultra-processed food consumption depend on the age these started to be consumed, and the total time of exposure.…”
Section: Alternative Study Designsmentioning
confidence: 99%